Cost of Production for Processed Oranges in Southwest Florida, 2014/15 - Ariel Singerman (EDIS, 2016)
UF/IFAS researchers collected data from twelve growers to estimate the cost of production per acre for processed oranges in southwest Florida during 2014/15. The cost estimates in this 4-page fact sheet do not represent any individual operation. Instead, their purpose is to serve as a benchmark for the Florida citrus industry. Typical users of these estimates include growers, consultants, property appraisers, and researchers. Written by Ariel Singerman and published by the Food and Resource Economics Department, December 2015.